PD-1 Blockade Reverses Obesity-Mediated T Cell Priming Impairment - Le, Catherine T.; Khuat, Lam T.; Caryotakis, Sofia E.; Wang, Marilyn; Dunai, Cordelia; Nguyen, Alan V.; Vick, Logan V.; Stoffel, Kevin M.; Blazar, Bruce R.; Monjazeb, Arta M.; Murphy, William J.; Soulika, Athena M. (Frontiers in Immunology, 2020)
Despite obesity reaching pandemic proportions, its impact on antigen-specific T cell responses is still unclear. We have recently demonstrated that obesity results in increased expression of PD-1 on T cells, and checkpoint blockade targeting PD-1/PD-L1 surprisingly resulted in greater clinical efficacy in cancer therapy. Adverse events associated with this therapy center around autoimmune reactions. In this study, we examined the impact of obesity on T-cell priming and on autoimmune pathogenesis using the mouse model experimental autoimmune encephalomyelitis (EAE), which is mediated by autoreactive myelin-specific T cells generated after immunization. We observed that diet-induced obese (DIO) mice had a markedly delayed EAE onset and developed milder clinical symptoms compared to mice on control diet (CD). This delay was associated with impaired generation of myelin-specific T cell numbers and concurrently correlated with increased PD-L1 upregulation on antigen-presenting cells in secondary lymphoid organs. PD-1 blockade during the priming stage of EAE restored disease onset and severity and increased numbers of pathogenic CD4+ T cells in the CNS of DIO mice to similar levels to those of CD mice. Administration of anti-PD-1 after onset of clinical symptoms did not increase EAE pathogenesis demonstrating that initial priming is the critical juncture affected by obesity. These findings demonstrate that obesity impairs antigen-specific T cell priming, but this can be reversed with PD-1 blockade. Our results further suggest that PD-1 blockade may increase the risk of autoimmune toxicities, particularly in obesity.